Analysis of Bicycle Path Infrastructure in Jakarta to Improve Cycling Comfort - Sunandar, Ali; Tia, Rahma Waldhani (Journal of World Conference (JWC), 2020)
The Provincial Government of DKI Jakarta is demanded to provide infrastructure and infrastructure that is environmentally friendly. one of the steps of the DKI Jakarta provincial government is to build bicycle lane infrastructure. Previously, the Government had built bicycle path infrastructure but it was not used as it functions. The purpose of this study is to determine the variables that most affect the infrastructure of the bicycle lane and provide suggestions for managing the variables that most influence so that bicycle lane users get the comfort of cycling so that the infrastructure is used properly and can reduce the level of air pollution in Jakarta. In this study, the authors used a quantitative research method by distributing questionnaires to respondents of active cyclists and passive cyclists. The questionnaire distributed contained variables of infrastructure facilities and infrastructure, and then the results of the questionnaire data which were primary data were processed using the Statistical Application Program. This research uses 4 stages of the questionnaire by using validity, reliability, descriptive test, Spearman correlation rank test, and regression test. The results of this study are the Bicycle Path Infrastructure in Jakarta has 3 variables that most influence in increasing the comfort of cyclists, there is the Evenness of the Path (49,4%), The Limiting of the Lane (33%), and the Existence of Markers(17.1%).